English Extensive Reading Practices in Nepalese Schools: A Case of An Institutional School in Nepal (Interdisciplinary Research in Education, 2025)
This study aims to discuss and evaluate the effectiveness of the extensive reading practices and the materials used in grade nine at Prithvi School (Pseudonym). The study was conducted using a case study design, focusing on the Extensive Reading activities of Grade Nine students and the ELT teacher. Classroom observation, semi-structured interview and Focus Group Discussion were the main data collection techniques. The data were analyzed and interpreted thematically. The study found that students accessed diverse materials but preferred literary texts, with teachers guiding selection to match proficiency and interest. Extensive Reading (ER) was embedded in daily lessons through interactive activities, learner choice, and teacher support, and extensive reading improved language skills, boosted confidence, and encouraged independent, motivated reading.